2013
DOI: 10.1038/ncomms2611
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the full-length HCV IRES in solution

Abstract: The 5 0 -untranslated region of the hepatitis C virus genome contains an internal ribosome entry site (IRES) that initiates cap-independent translation of the viral RNA. Until now, the structural characterization of the entire (IRES) remained limited to cryo-electron microscopy reconstructions of the (IRES) bound to different cellular partners. Here we report an atomic model of free full-length hepatitis C virus (IRES) refined by selection against small-angle X-ray scattering data that incorporates the known s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 59 publications
6
77
0
Order By: Relevance
“…In agreement with the results found for the FMDV IRES, OPW-Ru reactive positions tend to be located close to junctions, within flexible regions of the three-dimensional HCV IRES structure (Fig. 4B, inset) as defined by Perard et al (2013).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In agreement with the results found for the FMDV IRES, OPW-Ru reactive positions tend to be located close to junctions, within flexible regions of the three-dimensional HCV IRES structure (Fig. 4B, inset) as defined by Perard et al (2013).…”
Section: Resultssupporting
confidence: 79%
“…The potential correlation between structural features of both RNAs and reactivity toward OPWRu was also analyzed (Supplemental Tables 2, 3). We could not conclude that there is a direct correlation among the OPW-Ru reactivity and any of the structural features (solvent accessibility measured by OH-radical reactivity in both the HCV and FMDV IRES elements [Kieft et al 1999;Lozano et al 2014]; and interacting edges, sugar conformation, or backbone turn in the case of the HCV IRES element [Kieft et al 2002;Lukavsky et al 2003;Berry et al 2010;Perard et al 2013]). Concerning the type of secondary structure motif, a preferential attack to positions present in four-way junctions was observed (Figs.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Early structural work applied a 'divide and conquer' approach to determine three-dimensional structures of isolated IRES domains using NMR and X-ray crystallography [14,81]. By incorporating structures of known fragments, a recent study using SAXS and molecular dynamics simulations found that the free IRES is best fit by an ensemble of at least five conformations as a result of rigid domains moving with respect to one another by flexible linkers [95]. Many of the HCV IRES structural elements are conserved in related flaviviruses, as well as certain picornavirus genera, with variability especially in domain II and apical domain III regions [16].…”
Section: (A) the Pathways Of Hcv Ires-mediated Initiationmentioning
confidence: 99%
“…These observed positions of domain II are probably only a subset sampled during initiation, as a complete 48S complex of the 40S : IRES : eIF3 : eIF2-TC has yet to be solved. It has been proposed that the IRES must undergo a multi-step rearrangement during binary-complex formation to position domain II [95]; and clearly, for 80S ribosomes to transition into elongation, domain II must be entirely vacated from its E site position to make room for deacyclated initiator tRNA moving from the P site. The structural observations help explain the multipurpose role of domain II during tRNA recruitment and positioning, where it participates in both the formation of productive 48S complexes and the progression of 80S initiation complexes into elongation [82,129,131].…”
Section: (G) Dynamic Rearrangements Within the 80s : Ires Complexmentioning
confidence: 99%